O uso da classificação internacional de funcionalidade, incapacidade e saúde para crianças e jovens (CIF-CJ) na avaliação fonoaudiológica em ambiente ambulatorial - Marina Garcia de Souza Borges (2017)
Introduction: The International Classification of Functioning, Disability and Health Children & Youth Version (ICF-CY) was created by the World Health Organization (WHO) to describe the possible conditions of health and functionality of individuals aged up to 18 years and the characteristics that are proper of the development process. Its use has been reinforced by bodies such as the National Health Council (CNS) and the Federal Council of Speech Therapy (CFFa). However, its use in researches, and mainly in speech and language clinical practice in Brazil, is still very restricted. Purpose: To use the International Classification of Functioning, Disability and Health Children & Youth Version (ICF-CY) in the characterization of the functionality of patients assisted in a speech-language pathology outpatient clinic. Methods: This is a retrospective observational analytic cross-sectional study conducted at the Speech and Hearing Clinic of the São Geraldo Hospital, an integrant part of the complex of the Medical School (Hospital das Clínicas) of the Federal University of Minas Gerais (HC UFMG). The research was based on secondary data of anamnesis and evaluation reports of patients assisted from 2010 to 2014, configuring an initial corpus of 1032 medical records. Medical records of patients aged over 16 years and whose anamnesis or evaluation reports were incomplete were excluded. Information regarding socio demographic and clinical and assistance aspects of the patients was collected from the 556 records considered eligible for the initial analysis. In the next step, only medical records of patients aged from 5 to 16 years and without the suspected or confirmed diagnosis of hearing loss, intellectual disability, and global developmental disorders or without inconsistencies in relation to the data presented in the reports were included. Thereby, 180 medical records were analyzed using the ICF-CY in the classification of the functionality of the communication aspects and other speech-language disorders. For that, contents including categories of components such as Body Functions, Activities and Participation and Environmental Factors were identified in the reports. If present, they were analyzed as altered or not, indicating the existence of impairment, difficulty, Barrier or Facilitator. The next step focused on the categories pertaining to the Body functions and Activities and Participation identified, and an analysis was also carried out to establish factors that could represent a greater number of categories and verify the existence of their associations with socio-demographic and clinical and assistance aspects. For the data analysis, a description of the frequency distribution of the categorical variables, and the analysis of the measures of central tendency and dispersion for continuous variables were made. In order to reduce the number of ICF CY categories within the same component, a Factor Analysis was performed. To evaluate the existence of associations between the variables throughout the study, the Pearson Chi-square, Mann-Whitney and Kruskal-Wallis tests and the Spearman correlation were used. The adopted significance level was of 5%. Results: Initially, 556 medical records were included, being of 181 female and 375 male individuals, aged from one month to 16 years. The most frequent complaints in anamnesis were disorders in speech, written language and difficulty in social interaction, and the most prevalent diagnostic hypotheses were disorders in oral language, cognitive aspects of language and orofacial motricity. In the 180 medical records that met the criteria of the second stage, 65 categories of ICF-CY were identified. Among the 13 items of Body Functions verified, the category that was most frequently characterized as having impairment was the b167 - mental functions of language (69.4%), and the one that predominated with the description that no impairment was observed was the b156 - perceptual functions (82.0%). For the 34 categories identified pertaining to the component of Activities and Participation, the most frequently pointed out as difficulty were: d140 - learn to read - performance (84.9%) and d640 - performance of household tasks - performance (61.4%). The categories that, with higher percentage, were described as having no difficulty were: d155 - acquire skills/abilities – capacity (100.0%), d210 – perform a single task – capacity (100.0%), d550 – eat – capacity (100.0%) and d560 – drink - capacity (100.0%). Of the 18 categories related to Environmental Factors, the described one in most part of the reports as Barrier was the e425 - individual attitudes of acquaintances, peers, colleagues, neighbors and community members (25.6%) and the described ones as Facilitator with higher frequency were e130 - products and technology for education (100.0%), e165 - assets (100.0%), e310 - immediate family (100.0%) and e325 - acquaintances, peers, colleagues, neighbors and community members (100.0%). The Factor Analysis revealed two dimensions of the Body functions, being described the Factor one, denominated language/speech/hearing, formed by memory, perception, basic cognitive, mental of language, auditory and articulation functions, and the Factor two, related to orofacial motricity/voice, was formed by voice, respiratory and ingestion functions. For the analysis carried out with the categories of the Activities and Participation component, three factors were retained, being the Factor one, socialization formed by the management of the own behavior (Capacity and Performance), complex interpersonal interactions – performance and informal social relationships – performance, the Factor two was only formed by the capacity to acquire concepts, and the Factor three, family/school, formed by the performance in family relationships and school education. After analysis, a statistically significant association of the Factor one of the Body functions, language/speech/hearing, with the sociodemographic variables, education level of the patient, age, number of brothers, number of rooms at home and number of people at home were verified, as also with the clinical and assistance variables, complaint of speech alteration, diagnostic hypotheses of disorders of oral language acquisition/development, in the cognitive aspects of the language, speech and auditory processing, and with the conducts of complete evaluation of the auditory processing and speech therapy. The Factor two, orofacial motricity/voice, also integrant part of the Body functions, presented a statistically significant difference in relation to sociodemographic variable, education level of the father, and with the clinical and assistance variables, complaints of orofacial motricity disorders and social interaction, diagnostic hypotheses of orofacial motricity and voice disorders and conduct of referral for the follow-up with another professional. There was a statistically significant difference of the Factor one of the Activities and Participation, socialization, in relation to variables such as complaint of difficulty of social interaction and diagnostic hypothesis of disorders of the cognitive aspects of the language. For Factor two, acquisition of concepts, it was verified an association with statistical significance with complaints of speech disorders and difficulty of social interaction, diagnostic hypotheses of disorders in the cognitive aspects of language and orofacial motricity. Factor three, family/school, also constituted by categories of the component Activities and Participation, presented a statistically significant difference with the sociodemographic variables, education level of the patient, education level of the mother, education level of the father, place of residence and age and with the clinical and assistance variables, complaints of disorders in reading and writing issues/school difficulties and absence of speech disorders, professional that referred the patient to speech-language assessment and diagnostic hypotheses of disorders in issues of written language and absence of orofacial motricity disorders. Conclusion: This study showed that it was possible and feasible to use ICF-CY to characterize functional issues related to the speech and hearing aspects of children and teens referred to outpatient evaluation. It made also possible to verify the existence of associations between factors constructed through the most prevalent categories of the ICF-CY with sociodemographic and clinical and assistance variables. Thus, the possibility and importance of insertion of this classification in the outpatient clinic routine in speech therapy is demonstrated.